Experimental and modeling studies of a micro direct methanol fuel cell - Falcão, D. S. (2016)
The Direct Methanol Fuel Cell (DMFC) has attracted much attention due to its potential applications as a power source for transportation and portable electronic devices. Based on the advantages of the scaling laws, miniaturization promises higher efficiency and performance of power generating devices and the MicroDMFC is therefore an emergent technology. In this work, a set of experiments with a MicroDMFC of 2.25 cm2 active area are performed in order to investigate the effect of important operating parameters. Maximum power density achieved was 32 mW/cm2 using a 4 M methanol concentration at room temperature. Polarization curves are compared with mathematical model simulations in order to achieve a better understanding of how parameters affect performance. The one-dimensional model used in this work takes in account coupled heat and mass transfer, along with the electrochemical reactions occurring in a direct methanol fuel cell and was already developed and validated for DMFC in previous work by Oliveira et al. [1–3]. The model is also used to predict some important parameters to analyze fuel cell performance, such as water transport coefficient and methanol crossover. This easy to implement simplified model is suitable for use in real-time MicroDMFC simulations. More experimental data are also reported bearing in mind the insufficient experimental data available in literature at room temperature, a goal condition to use this technology in portable applications.